Inovasi Pembelajaran Pendidikan Agama Islam Berbasis Nilai-Nilai Syariat di MAN Aceh Jaya - Susanna, Susanna (Jurnal Ilmiah Guru Madrasah, 2025)
This study aims to analyze the innovation of Islamic Religious Education (PAI) learning based on sharia values at MAN Aceh Jaya as an integrative model that combines cognitive, affective, and spiritual dimensions. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving teachers, the principal, and students. The data were analyzed interactively through reduction, presentation, and conclusion drawing. The results indicate five major types of learning innovations: project-based learning, peer teaching, the use of Islamic digital media, outdoor learning, and spiritual reflection. These innovations integrate the values of aqidah, ibadah, and akhlaq within classroom and extracurricular activities. The implementation of sharia-based innovation increased students’ learning motivation, discipline, and religious awareness while strengthening the school’s religious culture. The study concludes that the success of innovation depends on the alignment between sharia values, teacher creativity, and institutional support. These findings provide a contextual model for developing Islamic Religious Education that is participatory, value-oriented, and character-based. Abstrak Penelitian ini bertujuan menganalisis inovasi pembelajaran Pendidikan Agama Islam (PAI) berbasis nilai-nilai syariat di MAN Aceh Jaya sebagai model pembelajaran yang integratif antara aspek kognitif, afektif, dan spiritual. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data diperoleh melalui observasi, wawancara mendalam, dan studi dokumentasi terhadap guru, kepala madrasah, dan siswa. Analisis data dilakukan secara interaktif melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan adanya lima bentuk utama inovasi pembelajaran, yaitu project-based learning, peer teaching, pemanfaatan media digital Islami, pembelajaran luar kelas, dan refleksi spiritual. Inovasi tersebut berfungsi sebagai sarana integrasi nilai aqidah, ibadah, dan akhlaq dalam proses belajar mengajar. Implementasi inovasi berbasis syariat terbukti meningkatkan motivasi belajar, kedisiplinan, dan kesadaran religius siswa, sekaligus memperkuat budaya religius madrasah. Penelitian ini menyimpulkan bahwa keberhasilan inovasi ditentukan oleh keselarasan antara nilai-nilai syariat, kreativitas guru, dan dukungan kelembagaan. Temuan ini berimplikasi pada pengembangan model pembelajaran PAI yang kontekstual, partisipatif, dan berkarakter Islami.